2018
DOI: 10.1111/1365-2656.12923
|View full text |Cite
|
Sign up to set email alerts
|

Taylor's power law captures the effects of environmental variability on community structure: An example from fishes in the North Sea

Abstract: Taylor's power law (TPL) describes the relationship between the mean and variance in abundance of populations, with the power law exponent considered a measure of aggregation. However, the usefulness of TPL exponents as an ecological metric has been questioned, largely due to its apparent ubiquity in various complex systems. The aim of this study was to test whether TPL exponents vary systematically with potential drivers of animal aggregation in time and space and therefore capture useful ecological informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 53 publications
6
25
0
Order By: Relevance
“…Indeed, a low corroboration of TPL was linked to a weak variance explanation of the regressions in Figure 1 (Supporting Information Figure S2). In the other traits, the range of trait expressions was similar to the variable range in other studies on TPL where strong TPL patterns were confirmed (Cobain et al, 2019;Kilpatrick & Ives, 2003). Therefore, we argue that in the mentioned traits the TPL slope is indeed close to one, indicating in these traits a Poisson random distribution of species traits in regional plant assemblages.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Indeed, a low corroboration of TPL was linked to a weak variance explanation of the regressions in Figure 1 (Supporting Information Figure S2). In the other traits, the range of trait expressions was similar to the variable range in other studies on TPL where strong TPL patterns were confirmed (Cobain et al, 2019;Kilpatrick & Ives, 2003). Therefore, we argue that in the mentioned traits the TPL slope is indeed close to one, indicating in these traits a Poisson random distribution of species traits in regional plant assemblages.…”
Section: Discussionsupporting
confidence: 83%
“…Previous authors have argued that TPL slopes vary systematically with environmental drivers that affect species abundances and spatial distributions (Cobain et al., 2019). In answer to our third question, our results corroborate this hypothesis in part.…”
Section: Discussionmentioning
confidence: 99%
“…|− ϵ + 1| is the scaling exponent of the distribution. B : Taylor’s law as scaling law between standard deviation and mean species abundance for five TRs; ν /2 is the scaling exponent of Taylor’s law that is typically construed by using the variance [ 72 ], 〈 x 2 〉 ∼ 〈 x 〉 ν ; smaller ν means that fluctuations in abundance are more even and species are more regularly distributed; vice versa, species are more power-law distributed (as supported by Zip’s law) driven by stronger environmental effects [ 85 ] (in this case ST) determining portfolio effects with potential stabilizing effects [ 86 ] (this however neglects interaction topology). All exponents for five TRs are interpolated by black dashed lines in insets to emphasize abundance patterns transitions across TRs/seasons; transitions show a gradual second-order phase transition with higher Pareto-distributed fluctuations for higher temperature.…”
Section: Resultsmentioning
confidence: 99%
“…|− ϵ + 1| is the scaling exponent of the distribution. B : Taylor’s law as scaling law between standard deviation and mean species abundance for five TRs; ν/ 2 is the scaling exponent of Taylor’s law that is typically construed by using the variance [54], ⟨ x 2 ⟩∼ ⟨ x ⟩ ν ; smaller ν means that fluctuations in abundance are more even and species are more regularly distributed; vice versa, species are more power-law distributed (as supported by Zip’s law) driven by stronger environmental effects [21] (in this case ST) determining portfolio effects with potential stabilizing effects [4] (this however neglects interaction topology). All exponents for five TRs are interpolated by black dashed lines in insets to emphasize abundance patterns transitions across TRs/seasons; transitions show a gradual second-order phase transition with higher Pareto-distributed fluctuations for higher temperature.…”
Section: Resultsmentioning
confidence: 99%